Concept of Balance in the Hindu-Balinese Community for Sustainable Tourist Park Spatial Planning - Muh. Fakhri Jamaluddin; Mohamad Sapari Dwi Hadian; Awaludin Nugraha (Gondang: Jurnal Seni dan Budaya, 2021)
The rapid development of Bali tourism sector, especially in the tourist area of Lake Batur, lead to many changes in community cultural patterns. Several issues, such as the transition of space functions and the development of tourism designations, have not considered the environmental, economic, social and cultural conditions in the local area. Several regional policies were established in order to maintain the local wisdom of the Hindu-Balinese community and become the basis for organizing tourism in Bali. The availability of open space in a tourist attraction in an destination can be a supporting factor for tourists and local communities. This was a qualitative descriptive study. This method aims to obtain an in-depth description regarding the forms of local wisdom of the Hindu-Balinese community which contain the elements of balance which further be adjusted into spatial planning. A sustainable tourist park may be a site for the activities and interaction among local community, tourists, and also be able to become a forum for education regarding Balinese culture and the natural environment, both of which need to be preserved for the sustainability of Lake Batur tourist area which has a great potential in the development of tourism sector.